Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0031264
|View full text |Cite
|
Sign up to set email alerts
|

S-LOCUS EARLY FLOWERING 3 Is Exclusively Present in the Genomes of Short-Styled Buckwheat Plants that Exhibit Heteromorphic Self-Incompatibility

Abstract: The different forms of flowers in a species have attracted the attention of many evolutionary biologists, including Charles Darwin. In Fagopyrum esculentum (common buckwheat), the occurrence of dimorphic flowers, namely short-styled and long-styled flowers, is associated with a type of self-incompatibility (SI) called heteromorphic SI. The floral morphology and intra-morph incompatibility are both determined by a single genetic locus named the S-locus. Plants with short-styled flowers are heterozygous (S/s) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 50 publications
2
80
0
1
Order By: Relevance
“…Two genes completely linked to the distyly locus have, however, been identified in buckwheat ( Fagopyrum esculentum ), and studies of plants from natural populations showed that some variants in these genes are specific to the S allele, which is strong evidence that recombination with the long style allele ( s ) is very rare (Yasui et al. ). This study sequenced about 610 kb around one of the genes, which included at least one other gene and also repetitive transposable element sequences; the repeats make assembly difficult, and the fully S‐linked region must be larger than the total length of current contigs.…”
Section: Flowering Plant Self‐incompatibilitymentioning
confidence: 99%
“…Two genes completely linked to the distyly locus have, however, been identified in buckwheat ( Fagopyrum esculentum ), and studies of plants from natural populations showed that some variants in these genes are specific to the S allele, which is strong evidence that recombination with the long style allele ( s ) is very rare (Yasui et al. ). This study sequenced about 610 kb around one of the genes, which included at least one other gene and also repetitive transposable element sequences; the repeats make assembly difficult, and the fully S‐linked region must be larger than the total length of current contigs.…”
Section: Flowering Plant Self‐incompatibilitymentioning
confidence: 99%
“…Efficient fertilization is only possible in inter-morph crosses. A candidate for a causal distyly gene has been described from Fagopyrum (Yasui et al, 2012); also, S- locus linked sequences have been identified from Primula and Turnera (Labonne and Shore, 2011; Labonne et al, 2009; Li et al, 2007, 2015; Nowak et al, 2015). However, in Primula no causal distyly gene has been isolated, and no plausible mechanistic explanation for style length dimorphism is available in any species, hampering progress in understanding the evolution of the S -locus supergene.
10.7554/eLife.17956.003Figure 1.Identification of CYP734A50 as an S-morph and style-specific gene.( A ) Dissected P. veris L- (left) and S-morph flowers (right), showing reciprocal differences in style length and anther position (yellow arrowheads).
…”
Section: Introductionmentioning
confidence: 99%
“…The tight linkage and convergent evolution of SI and floral characteristics in heterostylous plants have been attracting the interest of geneticists and evolutionary biologists since the age of Charles Darwin (Darwin, 1877). Many attempts to isolate the S gene have been reported in Primula, Fagopyrum, and Turnera, but the S gene has never been identified (Labonne and Shore, 2011;Li et al, 2011;Manfield et al, 2005;Yasui et al, 2012). We have also studied heterostyly in Linum in order to isolate the S gene and reported a good S gene candidate (Ushijima et al, 2012).…”
Section: Introductionmentioning
confidence: 99%